The Portable T.A. a problem solving guide - Elby, Andrew (Prentice-Hal, 1998)
*For introductory calculus-based physics courses. *Volume I covers Mechanics. Volume II covers Electricity and Magnetism. Suitable for use with any calculus-based physics text, this stand-alone collection of problems gives students extensive practice applying the central concepts of physics -- i.e., the ones most likely to "show up on tests." It includes exceptionally detailed solutions that explain the relevant concepts and problem-solving skills involved.